SEIR model and simulation research on unsafe psychological state propagation of construction workers considering safety climate and intimate relationships - Yuan, Ruijia; Zhang, Zhiwei; Deng, Xiaopeng; Li, Xiaosheng (Frontiers in Public Health, 2022)
The construction industry is a pillar industry of China and occupies an essential position in our economic development. However, in the fast-developing construction industry, the number of its safety accidents is also growing year by year. Safety accidents are often due to unsafe behaviors of construction workers, and unsafe precarious psychological states are important factors for unsafe behaviors. Therefore, this paper, based on a review of existing literature, uses the SEIR model and numerical simulation method to study the spread of unsafe psychological states among construction workers considering safety climate and intimate relationships. It puts forward corresponding countermeasures, which has great practical significance for reducing safety accidents in the construction industry. The results show that: (1) A good safety climate can help alleviate the spread of unsafe psychological states of construction workers. (2) The intimate relationship between construction workers will promote the association between communicable people and susceptible people, which will lead to the spread of an unsafe psychological state. (3) A larger network average will increase the spread speed and the density of infectious people, but will not increase the spread range. (4) Forgetting rate has a key role in the propagation of unsafe psychological states.Suggestions are made to hinder the propagation of these states, which will help to reduce the unsafe behavior of construction workers and the accident rate in the construction industry.